Guillain-Barré Syndrome following intravesical Bacillus Calmette-Guérin therapy for bladder cancer: a rare and intriguing case report - Khor, Vincent; Fahmy, Omar; Kheng, Christopher Siang Lee; Mohd Ghani, Khairul-Asri (Polish Urological Association, 2024)
Intravesical Bacillus Calmette-Guérin (BCG) therapy is a standard treatment for non-muscle invasive bladder cancer, but some patients experience side effects that lead to treatment discontinuation. Local side effects are typically mild, while systemic side effects can be severe and life-threatening. BCG therapy has immunotherapy effects on bladder cancer, but the mechanism is not fully understood. Due to its effect on the immune system, patients may also develop rare autoimmune complications, such as neuropathy. This case report suggests a potential association between BCG therapy and GuillainBarré Syndrome (GBS), as a patient developed GBS after receiving intravesical BCG therapy for invasive bladder cancer.